Calculation of the ideal isochronous field for the SC200 cyclotron using the Nelder-Mead simplex algorithm - Zhou, Kai; Song, Yun-Tao; Ding, Kai-Zhong; Chen, Gen; Karamysheva, Galina (Journal of nuclear science and technology, 2020)
In this paper, we propose a numerical method for ideal isochronous field calculation for the SC200 isochronous cyclotron based on the Nelder-Mead simplex algorithm. In this method, the radial field distribution is represented by an nth-order polynomial, an objective function is defined to describe the relative error of the orbital frequency, and the ideal isochronous field is calculated by optimizing the coefficients of the polynomial to minimize the objective function using the Nelder-Mead simplex algorithm. A comparative analysis of the proposed method and conventional methods indicates that the proposed method provides a more accurate ideal isochronous field, especially in the vicinity of the extraction region where the field flutter is large.